The rise of Islam - Curtis, Vesta Sarkhosh; Stewart, Sarah (Sarah Rosemary Anne) (Idea of Iran ;, 2009)
"The latest volume in the successful series The Idea of Iran addresses the impact made by Islam during and after the Arab conquest of Iran in the middle of the seventh century. How and why, once Iran had embraced the new religion, did it manage to retain its Persian language and distinctive Iranian identity once Muslim governance took hold? This conundrum, alongside other important questions, is addressed by the book, which includes seven distinguished contributions from leading scholars. Discussing a large variety of subjects which covers the whole spectrum of life in early Islamic Iran, the volume offers one of the most ambitious perspectives on Persian religion, society and culture to be published to date. It will be consulted by all students of Iranian history, and will be regarded as essential reading for scholars of Islam, the Middle East and medieval religion alike."--Jacket